THEORETICAL FUNDAMENTALS OF TEACHER'S PEDAGOGICAL CULTURE - Olena V. Bilonozhko (Alfred Nobel University Publisher, 2020)
The article is devoted to the theoretical investigation of the scientific issue of the teacher's pedagogical culture. The content of the definition of pedagogical culture, components of pedagogical culture are analyzed, the main systemic specific characteristics of pedagogical culture development are singled out, among which are the structure, unity, interaction, interdependence and multifacetedness. The components of pedagogical culture are given, such as: speech culture, mastery of pedagogical techniques, pedagogical skills, pedagogical improvisation, perceptual and suggestive abilities, pedagogical optimism, balance and demanding. Scientific views on the aspects of research of the pedagogical culture issues are systematized by scientists: socio-pedagogical, socio-historical and psychological-pedagogical ones. It is noted that the conceptual changes in the pedagogical culture of teachers are associated with changes in understanding the content, forms and directions of modern education. The pedagogical culture of the teacher is manifested in the ways of self-realization, self-affirmation and self-development, the development of personal, authorial norms of professional activity for the effective implementation of pedagogical activities. It is proved that the concept of pedagogical culture of a teacher has a pronounced systemic character and reflects the relationship between the concept of pedagogical competence and pedagogical culture. The article establishes relationship between the competencies of the professional activity of a teacher and the level of the pedagogical culture used in the European education system and fixed in the Concept of the new Ukrainian school in the framework of implementation of the goals of Bologna process. The components of the pedagogical culture of the teacher are determined: the system of knowledge, the ability to do emotional and value assessments, selfreflection, personal and professional growth throughout life